Real-Time Imaging VII 2003
DOI: 10.1117/12.477497
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a nonlinear gradient adaptive filter for processing of large-size medical sequences on general-purpose hardware

Abstract: To achieve significant noise reduction in medical images while at the same time preserving fine structures of diagnostic value, a non-linear filter called the multi-resolution gradient adaptive filter (MRGAF) was developed. Though the algorithm is well suited for its task of noise reduction in medical images, it is still limited to the application of offline processing in medical workstations due to its computational complexity. The aim of our study is to reach real-time processing of data from low-cost x-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This organization involved dividing an image into partitions called "super-lines," where each partition contained all the necessary information from each level of the multiresolution representation to allow the application of the algorithm in one pass. In [44], the results showed that after application of the super-line approach, only 0.2% of the memory accesses were to the external memory, which helped to achieve a processing rate of 43.6 fps for 512 × 512 images on a desktop GPP. Also, in [101], the results showed that the super-line approach was able to reduce the miss rate from 99% to 0.8%, achieving a processing rate of 44 fps for 555 × 382 images on a desktop GPP.…”
Section: Increasing Spatial/temporal Localitymentioning
confidence: 96%
See 2 more Smart Citations
“…This organization involved dividing an image into partitions called "super-lines," where each partition contained all the necessary information from each level of the multiresolution representation to allow the application of the algorithm in one pass. In [44], the results showed that after application of the super-line approach, only 0.2% of the memory accesses were to the external memory, which helped to achieve a processing rate of 43.6 fps for 512 × 512 images on a desktop GPP. Also, in [101], the results showed that the super-line approach was able to reduce the miss rate from 99% to 0.8%, achieving a processing rate of 44 fps for 555 × 382 images on a desktop GPP.…”
Section: Increasing Spatial/temporal Localitymentioning
confidence: 96%
“…In the never ending quest for a perfect picture, research in developing fast, high-quality algorithms for processing pictures/videos captured by consumer digital cameras or cell-phone cameras [80] is expected to continue well into the future. Of course, the developments in industrial inspection [25,34,67,135,147] and medical imaging systems [18,23,24,44,136,143,145] will continue to progress. The use of color image data [8,85,107,109], or in some cases, multispectral image data [139] in real-time image/video processing systems is also becoming an important area of research.…”
Section: Growth In Applications Of Real-time Image/video Processingmentioning
confidence: 96%
See 1 more Smart Citation